Geographical variation and local environment effects in the reproductive output and fecundity of the shrimp Exhippolysmata oplophoroides (Decapoda: Caridea) in southeastern Brazil - Stanski, Gilson [UNESP]; Carvalho, Mariana M. [UNESP]; Garcia, Joyce R. [UNESP]; Goncalves, Geslaine R. L. [UNESP]; Costa, Rogerio C. [UNESP]; Castilho, Antonio L. [UNESP] (Taylor & Francis Ltd, 2018)
We studied the shrimp Exhippolysmata oplophoroides in southeastern Brazil (Macae, 22037 '' 5; Ubatuba, 23 degrees 55 '' S; and Cananeia, 25 degrees 53 '' S) to test the hypotheses that (1) females should have the same reproductive output and fecundity at the regional scale, and (2) these reproductive parameters can vary among regions. Maximum carapace length (Macae = 13.1 mm, Ubatuba = 12.8, Cananeia = 16), fecundity, and reproductive output differed among regions (Ancova, p < 0.05). Females in Cananeia exhibited the highest reproductive output/fecundity (18.6%/5230 embryos), followed by those in Macae (16.0%/4365 embryos) and Ubatuba (12.6%/1206 embryos). We found that fecundity/reproductive output varies inversely with the length of the reproductive season, i.e. a considerable amount of energy is allocated during seasonal spawning periods in subtropical regions such as Cananeia. Previous studies have proved that E. oplophoroides is able to reproduce continuously in Ubatuba, with probably minor but continuous energy investment in reproduction occurring in this tropical region. In contrast, although Macae is located at tropical latitude, it is under the influence of Cabo Frio upwelling that alters the water's physical properties via cold water intrusion. This process may be a determining factor in the spawning seasonality of Macae's shrimp population, justifying the higher reproductive output recorded here than in Ubatuba.
Keywords: Bycatch; latitudinal pattern; marine front; Pleocyemata